Study Numerical Simulation of Stress-Strain Behavior of Reinforced Concrete Bar in Soil using Theoretical Models - Al Amli, Ali Sabah; Al-Ansari, Nadhir; Laue, Jan (Civil Engineering Journal, 2019)
Nonlinear analysis for reinforced concrete members (R.C.) with two types of bars also with unsaturated and saturated soils was used to represent the models. To control the corrosion in the steel bar that used in R.C. member and decrease the cost, the geogrid with steel bar reinforcement are taken in this study to determine the effect of load-deflection and stress-strain relationships. The finite element method is used to model the R.C. member, bars and soil. A three-dimensional finite element model by ABAQUS version 6.9 software program is used to predict the load versus deflection and stress versus strain response with soil. The results for the model in this study are compared with the experimental results from other research, and the results are very good. Therefore, it was concluded that the models developed in this study can accurately capture the behavior and predict the load-carrying capacity of such R.C. members with soil and the maximum stresses with strains. The results show plastic strain values in the R.C. member with saturated soil are larger than their values in unsaturated soil about (54%, 58%, and 55% and 52%) when the geogrid ratios are (without geogrid, 60%, 40% and 20%) respectively, with the same values of stresses.